Total plate count and yeast mold count in liquid traditional medicine (Jamu) sold in the sukoharjo region market - Jamilatun, Makhabbah; Lukito, Pradea Indah (International Journal of Basic and Applied Science, 2024)
Jamu is the name for traditional medicine from Indonesia. This liquid traditional medicine is made by boiling all the ingredients, then squeezing the juice and mixing it with boiled water. This simple process of making liquid traditional medicine can cause undesirable impacts, microbial contamination which can cause diseases such as Escherichia coli bacteria which can cause diarrhea. In Sukoharjo, in several areas, there are still many sellers of liquid traditional medicine selling their wares in the market. There is no information regarding the quality of this liquid traditional medicine. This research aims to determine microbial contamination in traditional medicinal liquids sold at the Sukoharjo Regional Market. Research methods include total plate count to determine bacterial contamination and yeast mold count to determine fungal contamination in the kencur rice liquid traditional medicine.  The results of calculating the total plate count showed that 3 samples exceeded the contamination limit with the highest total bacterial value of   Colony Forming Unit (CFU)/ml. The results of the research showed that from the calculation of yeast mold count, 9 samples exceeded the contamination limit with the highest total yeast mold value of  CFU/ml. This results can provide information to the public to increase awareness of consuming herbal medicine and to the local government to provide education to herbal medicine traders. There are still several traditional medicine quality standards that have not been observed in this study, so it is recommended that the quality of the types of microorganisms contamination, be further analyzed